2010
DOI: 10.1590/s1020-49892010000900012
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and health correlates of diabetes-related amputations at the Texas-Mexico border

Abstract: Objective. To examine the association between diabetes-related lower-extremity amputation (LEA) and ethnicity, age, source of payment, geographic location, diabetes severity, and health condition in adults with diabetes mellitus type 2 living in border and non-border counties in Texas, United States of America, and to assess intra-border region geographic differences in post-LEA treatment. Methods. This correlational study was based on secondary data from the 2003 Texas Inpatient Hospital Discharge Data. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In the general population, and within the diabetic population, the rate of LEA varies by geographic location, ethnic group, and type of community (rural/ urban) (28)(29)(30)(31). For developing countries, reported incidence rates for LEA secondary to diabetes vary from 13.7 to as high as 18.0 per 1 000 PY, as reported in studies conducted in the 1990s among Pima Indians (32,33).…”
Section: Discussionmentioning
confidence: 91%
“…In the general population, and within the diabetic population, the rate of LEA varies by geographic location, ethnic group, and type of community (rural/ urban) (28)(29)(30)(31). For developing countries, reported incidence rates for LEA secondary to diabetes vary from 13.7 to as high as 18.0 per 1 000 PY, as reported in studies conducted in the 1990s among Pima Indians (32,33).…”
Section: Discussionmentioning
confidence: 91%
“…Goodney and colleagues Louisiana. Even within the state of Texas, there is regional heterogeneity in number of amputations, with previous studies citing that the Texas-Mexico border and South Texas have higher rates of amputation compared with the rest of the state (11,15).…”
Section: Discussionmentioning
confidence: 99%
“…Texas is notable for high rates of underinsured individuals, increasing prevalence of diabetes, heterogeneity in regional poverty, and a growing Hispanic population (13). Prior studies have demonstrated that specific regions within Texas have relatively higher rates of LEAs (14,15). The purpose of the present analysis was to define the temporal trends and risk factor associations and assess the impact of revascularization therapy for LEAs in Texas.…”
mentioning
confidence: 99%
“…However, few studies have compared risk factors for diseases and mortality by border location. The few that have been conducted have focused on alcohol and drug abuse (Vaeth et al 2012; Shah et al 2012; Caetano et al 2012), birth defects (Lupo et al 2011), diabetes outcomes (Mier et al 2010), cancer screening (Fernández and Morales, 2007), and infectious disease risk (Pérez et al 2006). Moreover, most of these studies have made comparisons between cities or specific areas of the border/non-border, thereby failing to make the regional comparisons needed to best understand this dynamic.…”
Section: Introductionmentioning
confidence: 99%